2021
DOI: 10.1021/acs.macromol.1c01576
|View full text |Cite
|
Sign up to set email alerts
|

The Modulus of the Amorphous Phase of Semicrystalline Polymers

Abstract: A universal method for determining the modulus of the interlamellar amorphous phase of semicrystalline polymers was proposed. The basics of the method were presented on the example of high-density polyethylene (HDPE). The local deformation of the amorphous component was induced by the introduction of a swelling agent (hexane). The swelling-induced local strain and local stress of the interlamellar amorphous phase were estimated based on the changes of the long period and the yield stress, respectively. The det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…where, Em and Ea are the tensile modulus of semi-crystalline polymer and pure amorphous matrix, respectively, and k = ρm/ρcXc. Ea is reported to be 3 MPa in HDPE and accordingly, Ec was calculated to be 1.611 GPa [35].…”
Section: Mechanical Characteristics Of the Nanocompositesmentioning
confidence: 99%
“…where, Em and Ea are the tensile modulus of semi-crystalline polymer and pure amorphous matrix, respectively, and k = ρm/ρcXc. Ea is reported to be 3 MPa in HDPE and accordingly, Ec was calculated to be 1.611 GPa [35].…”
Section: Mechanical Characteristics Of the Nanocompositesmentioning
confidence: 99%
“…FEM model calculations performed for the oriented block copolymer structure [ 55 ] demonstrated that the first sinusoidal undulations were generated when the ratio of the elastic moduli exceeded 500 (at constant layer thickness). In semicrystalline polymers deformed above T g , this ratio is expected to be much higher (e.g., in polyethylene, PE, an overall modulus of elasticity of crystalline phase is about 50 GPa—elastic constants calculated for anisotropic PE crystal range from c 11 ≈ c 22 ≈ 10 GPa to c 33 ≈ 300 GPa [ 60 ], while that of amorphous layer is below 40 MPa [ 61 ], i.e., smaller by 3 order of magnitude), which can indicate their high susceptibility to microbuckling upon deformation.…”
Section: Resultsmentioning
confidence: 99%
“…It also calls into question the applicability of the Gibbs–Thomson equation [ 74 ], which relates broad melting peaks of polymers to the thickness distribution of their crystalline lamellas. In the last few years, more and more evidence [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ] contributing to the opinion that the distribution of lamellar thickness cannot fully explain the melting behavior of semicrystalline polymers appeared. For example, crystallites of the same size can melt at different temperatures depending on the thickness of adjacent amorphous regions [ 75 ].…”
Section: Resultsmentioning
confidence: 99%